Growth, Structural Transformation, and Rural Change in Viet Nam: A Rising Dragon on the Move - Tarp, Finn (WIDER Studies in Development Economics, 2017)
Many developing countries-Viet Nam included-continue to struggle to raise incomes per capita. A common feature of the growth and development process is a fundamental change in the pattern of economic activity, as households reallocate labour from traditional agriculture to more productive forms of agriculture and modern industrial and service sectors. Broad structural transformation and widespread poverty reduction is the combined result of these large-scale shifts in work and labour allocation when they realize desired development goals. The roots of this book grow from when the first pilot Viet Nam Access to Resources Household Survey (VARHS) was carried out in 2002. The success of this inspired the Central Institute of Economic Management (CIEM) in Hanoi, the Institute of Policy and Strategy for Agriculture and Rural Development (CAP-IPSARD), the Institute of Labour Science and Social Affairs (ILSSA), and the Development Economics Research Group (DERG) of the University of Copenhagen, together with Danida and, later on, UNU-WIDER, to plan and carry out a more ambitious VARHS from 2006, increasing coverage and representativeness to more than 2,150 families and 12 provinces across the various regions of Viet Nam. The VARHS covering these very same households had, by 2014, been carried out five times, that is, every two years. It is on this high-quality panel data foundation and almost fifteen years of study and policy work using the VARHS data that the present volume builds, in its effort to bring out the essential rural microeconomic characteristics and insights of a dynamic South-East Asian economy in transition from a centrally planned towards a more market-based economy.